2015
DOI: 10.1007/s00216-015-8938-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ginkgo biloba supplements adulteration using high performance thin layer chromatography and ultra high performance liquid chromatography-diode array detector-quadrupole time of flight-mass spectrometry

Abstract: Ginkgo biloba is one of the most widely sold herbal supplements and medicines in the world. Its popularity stems from having a positive effect on memory and the circulatory system in clinical studies. As ginkgo popularity increased, non-proprietary extracts were introduced claiming to have a similar phytochemical profile as the clinically tested extracts. The standardized commercial extracts of G. biloba leaf used in ginkgo supplements contain not less than 6% sesquiterpene lactones and 24% flavonol glycosides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 19 publications
3
32
0
Order By: Relevance
“…This point is especially important as the presented results represent the first unambiguous proof that genistein is indeed a naturally occurring constituent of G. biloba leaves ( Figure 9) and by extension of the respective extract products -and therefore not prove of adulteration as claimed in previous publications [3,4]. Whereas these previous publications exclusively concentrated on commercially purchased G. biloba leave extracts, the preparation of which the authors had no influence on, all extract samples examined in the paper at hand were prepared in house at Zhejiang CONBA from leave samples collected personally by the authors.…”
supporting
confidence: 60%
“…This point is especially important as the presented results represent the first unambiguous proof that genistein is indeed a naturally occurring constituent of G. biloba leaves ( Figure 9) and by extension of the respective extract products -and therefore not prove of adulteration as claimed in previous publications [3,4]. Whereas these previous publications exclusively concentrated on commercially purchased G. biloba leave extracts, the preparation of which the authors had no influence on, all extract samples examined in the paper at hand were prepared in house at Zhejiang CONBA from leave samples collected personally by the authors.…”
supporting
confidence: 60%
“…It has been reported that commercial ginkgo extracts may be adulterated with other flavonoid-rich extracts to increase their flavonoid content [18,19]. Chandra et al [19] recommended the combination of a qualitative determination of unhydrolyzed extracts as well as a quantitative analysis for total flavonol glycosides, including quercetin/kaempferol/isorhamnetin ratios, in hydrolyzed extracts to establish or track the authenticity of extracts.…”
Section: Samplementioning
confidence: 99%
“…Chandra et al [19] recommended the combination of a qualitative determination of unhydrolyzed extracts as well as a quantitative analysis for total flavonol glycosides, including quercetin/kaempferol/isorhamnetin ratios, in hydrolyzed extracts to establish or track the authenticity of extracts. Similarly, Avula et al [18] considered that measurement of the flavonoid composition without a prior hydrolysis step is a good analytical approach because it can provide assurance that the supplement has not been adulterated with either flavonol aglycones or flavonol glycosides.…”
Section: Samplementioning
confidence: 99%
“…The most common form of ginkgo adulteration is spiking with pure flavonoids (rutin and quercetin), hydrolyzed extracts or extracts from other flavonoid‐rich material such as Japanese sophora ( Styphnolobium japonicum )31 in order to comply with the compendial requirement for not less than 22% of flavonol glycosides. The limits for the content of rutin (not more than 4%) and quercetin (not more than 0.5%) was introduced in the compendia to detect these adulterated products 26.…”
Section: Usp Dietary Supplement Standardsmentioning
confidence: 99%